2018
DOI: 10.1002/aoc.4234
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of nickel(II), copper(II) and oxovanadium(II)‐dihydroindolone complexes towards homogeneous oxidation reactions

Abstract: Three novel paramagnetic metal complexes (MH 2 ID) of Ni 2+ , Cu 2+ and VO 2+ ions with 3-hydroxy-3,3'-biindoline-2,2'-dione (dihydroindolone, H 4 ID) were synthesized and characterized by different spectroscopic methods. The ligand (H 4 ID) was synthesized via homocoupling reaction of isatin in presence of phenylalanine in methanol. Complexation of low valent Ni 2+ , Cu 2+ ions and high valent VO 2+ ions with H 4 ID carried out in 1: 2 molar ratios. A comparison in the catalytic potential of paramagnetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 54 publications
4
25
0
1
Order By: Relevance
“…K b is displayed for the strength of the interaction binding between HLn, PdLn, or Co (Ln) 2 and the different concentrations of ctDNA. K b could be obtained derived within Equation 5and by plotting of the [DNA]/(ε a À ε b ) ratio versus the different concentrations of ctDNA [ctDNA], as given before [19] :…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…K b is displayed for the strength of the interaction binding between HLn, PdLn, or Co (Ln) 2 and the different concentrations of ctDNA. K b could be obtained derived within Equation 5and by plotting of the [DNA]/(ε a À ε b ) ratio versus the different concentrations of ctDNA [ctDNA], as given before [19] :…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%
“…[34] Despite the intensive studies of palladium complexes as effective catalysts for cross-coupling biaryl formation, they were not explored as favored catalysts for organic redox processes, for example, alkenes, alkanes, alcohols, and thiols oxidation. Furthermore, comparing to those of aryl and aroyl hydrazones, [19] the catalytic influence of the metallated forms of isatin-hydrazones was less concerned in alternative catalytic processes, significantly redox systems. Isatin-hydrazones are well known with less solubility in most organic solvents as non-ecological reagents; hence, synthesis of a new class of isatin-hydrazones and their metallated compounds, as ecofriendly with water solubility, is an environmental demand.…”
Section: Introductionmentioning
confidence: 99%
“…No formation of epoxide was observed without the addition of H 2 O 2 (Table 2, entry 6). Then again, only 15.5% conversion of cyclooctene to the corresponding epoxide was obtained in the presence of H 2 O 2 as a sole catalyst and oxidant (Table 2, entry 7), 65,66 which in turn justifies the importance of both MOF and H 2 O 2 in the epoxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of III B could be more acceptable for VO(acac)(L) due to the presence of a high reactive acetylacetonate ligand [20,50]. This suggestion has been studied by Nunes et al [41] donor atom electrochemical contribution to redox potentials (DEC) of the O ac (acetylacetonate-enolic oxygen) compared to N py (pyridine nitrogen) in the square pyramidal vanadyl complexes is an important study to measure the VO-complexes reactivity toward catalytic oxidation processes as reported by Keramidas et al [51] and by our previous work [52,53]. This could be a highly acceptable reason for the higher catalytic activity of VO(acac)(L) compared to VO(L) 2 in the (ep)oxidation processes of cis-cyclooctene or 1,2-octene homogeneously.…”
Section: The Mechanistic Aspectsmentioning
confidence: 97%